Underpricing Phenomenon of Public Offering of Shares: A Theoretical and Empirical Review - Gurung, Jas Bahadur; Sharma, Dilli Raj (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
This study aims to review the extant literature on underpricing of initial public offerings and its determining factors using systematic review by selecting quality papers from the Web of Science, Scopus and Google Scholar databases. The study investigates major theories and the past empirical works undertaken across global markets. The study shows that the level of underpricing of IPOs is the lowest in the developed markets, moderate in the emerging markets, and it is the highest in the Middle East countries. In case of Nepal, very limited empirical literature has been documented, where IPOs are highly underpriced and largely oversubscribed. The review also indicates that no single effort of identifying the ‘hot issue’ market is made in the academic community. Additionally, the analysis of sectoral and year-wise underpricing is totally ignored in the Nepali studies. Prior studies of Nepal are yet to identify the important factors that influence deeper initial underpricing of IPOs. In essence, they failed to test the theoretical explanations of IPO underpricing in the Nepali context. Thus, this review suggests that there is an urgent need of undertaking studies considering common methodologies to test the existing theories that could be beneficial to investors, policy makers, issuing firms, and market intermediaries. Besides, future researchers can conduct review of underpricing phenomenon employing sophisticated research designs like bibliometric analysis and meta-analysis to explore niche area of research in this field.